Three new species of the spider genus Nopsma (Araneae, Caponiidae, Nopinae) from Colombia (2021)
Three new Colombian species of the spider genus Nopsma Sánchez-Ruiz, Brescovit & Bonaldo, 2020 are described and illustrated: Nopsma leticia sp. nov. (male) from Amazonas department, Nopsma macagual sp. nov. (male) from Caquetá department and Nopsma paya sp. nov. (male and female) from Putumayo department. The collection data of the holotype of Nopsma florencia Sánchez-Ruiz, Brescovit & Bonaldo are corrected. Additionally, an updated identification key for all species of the genus and a distribution map for the Colombian species are included